KEUNGGULAN KOMPARATIF SEKTOR PERIKANAN - , Harsa Multiar, Prof. Tri Widodo, M.Ec.Dev., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The purpose of this research is to determine the comparative advantages and Product Mapping of export Indonesian fishery products. The outcome of this research is expected to be useful in the production of fishery products and trade policy formulation, and for science, especially regarding the analysis of RCA in Indonesia. The data that used are secondary information, particularly from UN-COMTRADE and fishery statistics published by the Ministry of Maritime Affairs and Fisheries. The problem in this study were analyzed by using the Normalized Revealed Comparative Advantage (NRCA) and the Product Mapping. The research has shown that for the products of crustaceans, molluscs and aquatic invertebrates have a comparative advantage, but showed a declining trend. While other products showed a rising trend although it does not have a comparative advantage. There are 14 fishery products that have comparative advantages and Indonesia as a net exporter of these products in 2012. Only a few provinces in Indonesia which have a comparative advantage in the export of fishery products.